2021
DOI: 10.3390/su132413674
|View full text |Cite
|
Sign up to set email alerts
|

Examining Emotional Labor in COVID-19 through the Lens of Self-Efficacy

Abstract: The ongoing COVID-19 pandemic has dealt a significant blow to the restaurant industry, with many restaurants suspending operations or closing altogether. This study was aimed to investigate the effects of emotional labor on employees’ well-being and the mediating role of self-efficacy in the context of chain restaurants. Data were collected in 2020 through an online survey in China, and results revealed that emotional labor had a significant impact on well-being that was measured in life and job satisfaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 63 publications
1
8
0
6
Order By: Relevance
“…Indeed, mutual recognition respect, an equality-based respect, can be regarded as a central ingredient for promoting organizational sustainability and also for maintaining an innovative workforce. Meanwhile, in today's competitive work environment, and despite other challenges [4], leaders have to deal with employees who view their exchanges as biased and inequitable. For instance, psychologically entitled employees believe they deserve preferential treatment irrespective of their performance [5].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, mutual recognition respect, an equality-based respect, can be regarded as a central ingredient for promoting organizational sustainability and also for maintaining an innovative workforce. Meanwhile, in today's competitive work environment, and despite other challenges [4], leaders have to deal with employees who view their exchanges as biased and inequitable. For instance, psychologically entitled employees believe they deserve preferential treatment irrespective of their performance [5].…”
Section: Introductionmentioning
confidence: 99%
“…The findings demonstrated that emotional labor significantly affects wellbeing, as shown by life and job satisfaction. Self-efficacy plays a crucial mediating function between deep behavior and life happiness, as well as having a major positive impact on employees' work and personal well-being [ 8 ]. Kowal asserted that emotional labor is necessary in the majority of vocations and connected participants' emotional labor and self-efficacy to recruiting [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…이러한 제한들은 사회적 불평등을 극화시키고 시민들의 소외와 고립감을 고조시켰다 [1]. 공공 서비스에 대한 시민들의 불편감과 불만은 공공 근로자의 감정노동으로 이어진다 [1][2][3]. 코로나19로 인해 심리적 스트레스 수준이 높아진 그리고 제한에 예민해진 사람들이 공공 근로자에게 어려운 요구를 강요하고 부정적 감정을 표출하게 된 것이었다 [2] [3].…”
Section: 서론unclassified